(untitled) (Third Sector Social Economic Review, 2020)
The aim of this study is to determine the effect of the competitive strategies applied by the health institutions providing services in the field of medical tourism to the performance of health institutions. 102 health institutions in Istanbul were determined as the sample of the research. In the selection of the sample, convenience sampling method, a type of random sampling technic, was used. The data obtained from the questionnaires presented to the managers of health institutions were analyzed using SPSS 22 package program. As a result of the research, differentiation strategy has a very low and positive effect on performance. It is concluded that the focus strategy and cost leadership strategy have no impact on performance. In order to make sense of the analysis results, data were collected again through the interview technique. The results obtained in the quantitative part of the study are also confirmed in the qualitative part of the study.